Catalytic oxidation mechanisms of carbon monoxide over single- and double-vacancy Mn-embedded graphene. (27th May 2020) - Luo, Mingming; Liang, Zhao; Chen, Mingwei; Peera, Shaik Gouse; Liu, Chao; Yang, Hui; Qi, Xiaopeng; Liu, Juan; Liang, Tongxiang
Abstract : CO oxidation on MnC3 and MnC4 has fast kinetics and a low energy barrier. Abstract : Single-atom catalysts (SACs) have been extensively investigated in recent times due to their highly dispersed atomic levels and the improved distribution of their metallic active sites, maximizing the specific activity of the catalysts. Through density functional theory (DFT) calculations, the carbon monoxide oxidation reaction (COOR) on Mn atoms embedded in single- and double-vacancy graphene was investigated (MnC3 and MnC4 ). For MnC3, COOR may occur via the Eley–Rideal (ER) and Langmuir–Hinshelwood (LH) mechanisms, and the corresponding energy barriers of the rate-determining step (RDS) at 0 K are 0.832 and 0.829 eV, respectively. COOR prefers to react via the LH mechanism and the energy barrier of the RDS is 0.761 eV at room temperature (298.15 K). For MnC4, COOR prefers to follow the LH mechanism with an energy barrier of 0.568 eV at 0 K. The CO oxidation reaction on MnC3 and MnC4 has fast kinetics and the reaction time of the RDS is less than 1 s. These results indicate that MnC3 and MnC4 are promising CO oxidation catalysts.